Ancestry of the Indian Population Determined by Y Chromosome Markers - De, Jhilik (My University, 2001)
Seven microsatellites, DYS 388, DYS 3891, DYS 389II, DYS 390, DYS 391, DYS 392 and DYS 393 and a biallelic locus DYS 271 were analyzed in the Indian population with the aim of understanding the relationships of the Indo-European and the Dravidian population of India with those of the European /Central Asian populations. The 116 Indian samples, used in the study, enjoy a wide geographical distribution and represents well the different religions and caste groups of India. Supporting previously published results, most variation is found between populations within continents than between continents. No significant differences were found between the different religious and caste groups of India with those of the World populations. All the alleles of the different markers are well represented in the different ethnic groups of India, and thus, does not support the popular belief that the highest diversity exists within the middle caste. Significant differences in the distribution of alleles are found in different regions of India especially between the North and the South. A phylogenetic relationship appears to exist between the Sindhis from South Pakistan with those of the South Indian population. This lends support to the belief that the present population from Sind might represent a remnant population of the original inhabitant of the region that was mainly pushed further to the Southern part of Subcontinent by later invasions. A phylogenetic relationship also exists between the Indian population and the Burushaski population from Northwest Pakistan and with the Kazakhs, Kirgiz and the Uighurs from Central Asia. This is in agreement with previously published results, and supports the occurrence of two main population movements from Central Asia into India at different time intervals that gave birth to the two main language families-the Dravidian and the Indo-European languages in India.
Keywords: India; ancestry; chromosome; marker; population